A pore-expanded supramolecular organic framework and its enrichment of photosensitizers and catalysts for visible-light-induced hydrogen production. Issue 10 (25th April 2019) - Yan, Meng; Liu, Xu-Bo; Gao, Zhong-Zheng; Wu, Yi-Peng; Hou, Jun-Li; Wang, Hui; Zhang, Dan-Wei; Liu, Yi; Li, Zhan-Ting
Abstract : A 3.6 nm-pore SOF is constructed, which adsorbs both photosensitizers and polyoxometallates for visible light-induced proton reduction to produce H2 . Abstract : A pore-expanded three-dimensional supramolecular organic frameworkSOF-bpb, with a previously unattained aperture size of 3.6 nm, has been constructed in water from the co-assembly of cucurbit[8]uril (CB[8]) and a tetraphenylmethane-cored 1, 4-bis(pyridin-4-yl)-benzene-appended building blockM1 . The periodicity ofSOF-bpb in water and in the solid state has been confirmed using synchrotron X-ray scattering and diffraction experiments.SOF-bpb can adsorb anionic and neutral Ru 2+ complex photosensitizers and anionic Wells–Dawson-type and Keggin-type polyoxometalates (POMs). The adsorption leads to an important enrichment effect, which remarkably increases the catalytic efficiency of the Ru 2+ complex–POM systems for visible light-induced reduction of protons to produce H2 . The expanded aperture ofSOF-bpb also facilitates light absorption of the adsorbed Ru 2+ complex photosensitizers and electron transfer between excited complexes and the POM catalysts, leading to enhanced photocatalytic activities as compared with the prototypical SOF that has an aperture size of 2.1 nm.